Предмет: Математика, автор: alikhan2287

памагите пожалуйста ​

Приложения:

Ответы

Автор ответа: axatar
1

Ответ:

3

Пошаговое объяснение:

\frac{(\frac{7}{15}- \frac{3}{40}-\frac{1}{24}):0,7}{(2,4* \frac{1}{3}-3)*\frac{5}{11} } *\frac{1\frac{5}{6}:(\frac{3}{4}-1\frac{2}{3})}{(\frac{4}{9}-\frac{5}{12}+0,75)*\frac{3}{7} } =3

1)(\frac{7}{15}- \frac{3}{40}-\frac{1}{24}):0,7=\frac{7*8-3*3-1*5}{120}:\frac{7}{10}= \\\\=\frac{56-9-5}{120}*\frac{10}{7}=\frac{42}{120}*\frac{10}{7}=\frac{6}{12}=\frac{1}{2}

2)(2,4* \frac{1}{3}-3)*\frac{5}{11} =(2,4:3-3)*\frac{5}{11} =(0,8-3)*\frac{5}{11} =\\\\=-2,2*\frac{5}{11}=-\frac{22}{10} *\frac{5}{11}=-\frac{2}{2}=-1

3)1\frac{5}{6}:(\frac{3}{4}-1\frac{2}{3})=\frac{11}{6}:(\frac{3}{4}-\frac{5}{3})=\frac{11}{6}:\frac{3*3-5*4}{12}=\frac{11}{6}:\frac{9-20}{12}=\\\\=\frac{11}{6}:\frac{-11}{12}=\frac{11}{6}*\frac{-12}{11}=-2

4)(\frac{4}{9}-\frac{5}{12}+0,75)*\frac{3}{7} =(\frac{4*4-5*3}{36}+\frac{75}{100})*\frac{3}{7} =(\frac{16-15}{36}+\frac{3}{4})*\frac{3}{7} =\\\\=(\frac{1}{36}+\frac{3}{4})*\frac{3}{7} =\frac{1+3*9}{36}*\frac{3}{7} =\frac{28}{36}*\frac{3}{7} =\frac{4}{12}=\frac{1}{3}

5)\frac{\frac{1}{2}}{-1} *\frac{-2}{\frac{1}{3} } =\frac{-1}{2} *\frac{-2*3}{1} =3

Похожие вопросы
Предмет: Алгебра, автор: naka04054840
Предмет: Биология, автор: lijeiwowa